Experimental study of crack resistance and strength of oblique planes of reinforced concrete point-force loaded beams with positive and negative bending moment diagram - Maksymovych, S. B. (Видавництво Львівської політехніки, 2015)
The paper discusses experimental study of oblique planes of reinforced concrete solid beams at simultaneous exertion of constant transverse force and positive and negative bending moments. The tested beams had similar characteristics and differed only in types of reinforcement of oblique planes. Analysis of experimental results revealed the specifics of development and width of oblique cracks in the zone of effect of constant transverse force and positive and negative bending moments. The dynamics of development and width of oblique cracks depending on the load was recorded. The study also assessed the effect of various types of oblique planes reinforcement on bearing capacity of the beams. The experiments showed that nucleation of oblique cracks in beams with positive and negative bending moment diagram for the relationship a/d = 1 occurs at mid-height of the beam. Distribution of stresses along the tension longitudinal reinforcement of beams is different from the theoretical bending moment diagram. In beams with positive and negative bending moment diagram at the relationship a/d = 1, horizontal (transverse) reinforcement is the most effective type of transverse reinforcement in terms of bearing capacity of oblique planes and width of oblique cracks. Розглянуто експериментальні дослідження похилих перерізів нерозрізних залізо- бетонних балок за одночасної дії постійної поперечної сили і двозначних моментів. Випробувані балки мали одинакові характеристики і відрізнялися тільки видами армування похилих перерізів. Під час аналізу експериментальних досліджень виявлено специфіку утворення і ширини розкриття похилих тріщин у зоні дії постійної поперечної сили і двозначного згинального моменту. Зафіксована динаміка розвитку та ширина розкриття похилих тріщин залежно від навантаження. Виявлено також вплив різних видів армування похилих перерізів на несучу здатність балок. Експерименти показали, що зародження похилих тріщин у балках з двозначною епюрою згинальних моментів за відношення a/d = 1 проходить у середині висоти балки. Розподіл напружень по довжині розтягнутої поздовжньої арматури балок не відповідає теоретичній епюрі згинальних моментів. У разі двозначної епюри згинальних моментів та відношенні a/d = 1 найефективнішою поперечною арматурою, з огляду на несучу здатність похилих перерізів і ширину розкриття похилих тріщин, є горизонтально розміщена поперечна арматура.
Keywords: reinforced concrete beam; oblique planes; positive and negative bending moment diagram; залізобетонні балки; похилі перерізи; двозначна епюра згинальних моментів